Addition of probenecid to oral β-lactam antibiotics: a systematic review and meta-analysis. (21st June 2022) - Wilson, Richard C; Arkell, Paul; Riezk, Alaa; Gilchrist, Mark; Wheeler, Graham; Hope, William; Holmes, Alison H; Rawson, Timothy M
Abstract: Objectives: To explore the literature comparing the pharmacokinetic and clinical outcomes from adding probenecid to oral β-lactams. Methods: Medline and EMBASE were searched from inception to December 2021 for all English language studies comparing the addition of probenecid (intervention) with an oral β-lactam [flucloxacillin, penicillin V, amoxicillin (± clavulanate), cefalexin, cefuroxime axetil] alone (comparator). ROBINS-I and ROB-2 tools were used. Data on antibiotic therapy, infection diagnosis, primary and secondary outcomes relating to pharmacokinetics and clinical outcomes, plus adverse events were extracted and reported descriptively. For a subset of studies comparing treatment failure between probenecid and control groups, meta-analysis was performed. Results: Overall, 18/295 (6%) screened abstracts were included. Populations, methodology and outcome data were heterogeneous. Common populations included healthy volunteers (9/18; 50%) and those with gonococcal infection (6/18; 33%). Most studies were crossover trials (11/18; 61%) or parallel-arm randomized trials (4/18; 22%). Where pharmacokinetic analyses were performed, addition of probenecid to oral β-lactams increased total AUC (7/7; 100%), C max (5/8; 63%) and serum t ½ (6/8; 75%). Probenecid improved PTA (2/2; 100%). Meta-analysis of 3105 (2258 intervention, 847 control) patients treated for gonococcal disease demonstrated a relative risk of treatment failure in the random-effects model of 0.33 (95% CI 0.20–0.55; I 2  = 7%), favouring probenecid. Conclusions: Probenecid-boosted β-lactam therapy is associated with improved outcomes in gonococcal disease. Pharmacokinetic data suggest that probenecid-boosted oral β-lactam therapy may have a broader application, but appropriately powered mechanistic and efficacy studies are required.